Die amerikanischen Arten der Gattungen Euopius, Gnaptodon und Pseudognaptodon (Hymenoptera: Braconidae). - Fischer, Maximilian (Contributions to Entomology = Beiträge zur Entomologie, 1967)
The American species ofthe genera Euopius, Gnaptodon and Pseudognaptodon(Opiinae) are revised and keys are given. The name of the genus Neopius is changed into Euopius, because Neopius carinaticeps Gahan is synonymous with Opius rudis Wesmael. New descriptions are given of Euopius foveolaris, E. recurrentis, E. scutellaris, E. simplificatus and Gnaptodon novateutonicus, and they are compared with closely related forms. A redescription is given of Pseudognaptodon minutus (Ashmead). The genus Gnaptodon Haliday is first noted for the neotropical region. Nomenclatural Acts foveolaris Fischer, 1967 (Euopius), spec. n. recurrentis Fischer, 1967 (Euopius), spec. n. scutellaris Fischer, 1967 (Euopius), spec. n. simplificatus Fischer, 1967 (Euopius), spec. n. novateutonicus Fischer, 1967 (Gnaptodon), spec. n.